Phase 3 trial of sequential versus combination treatment in colorectal cancer: The C-cubed study. (July 2022) - Inada, Ryo; Nagasaka, Takeshi; Shimokawa, Mototsugu; Ojima, Hitoshi; Noura, Shingo; Tanioka, Hiroaki; Munemoto, Yoshinori; Shimada, Yasuhiro; Ishibashi, Keiichiro; Shindo, Yoshiaki; Mishima, Hideyuki; Okajima, Masasumi; et al.
Abstract: Background: An optimal treatment strategy using oxaliplatin and bevacizumab for metastatic colorectal cancer has not been defined. We investigated whether the sequential treatment using fluoropyrimidines with bevacizumab followed by the addition of oxaliplatin at first progression was better than a combination treatment using fluoropyrimidines and oxaliplatin with bevacizumab. Methods: In the sequential treatment, the escalation from fluoropyrimidines plus bevacizumab to fluoropyrimidines plus oxaliplatin with bevacizumab was recommended in case of progressive disease. Time to failure of strategy was the primary end-point, whereas the secondary end-points were overall survival, progression-free survival, overall response rate and safety. Results: Three hundred patients with previously untreated metastatic colorectal cancer were randomised to receive either the sequential treatment (n = 151) or the combination treatment (n = 149). The sequential treatment was superior to the combination treatment about time to failure of strategy (15.2 months; 95% CI, 12.5–17.2 months vs. 7.8 months: 95% CI, 6.3–9.5 months; P  < 0.001). However, the median overall survival was 27.5 (95% CI, 24.4 to 32.7) months in the sequential treatment and 27.0 (95% CI, 22.8 to 36.0) months in the combination treatment (hazard ratio, 0.92; 95% CI, 0.66 to 1.28; P  = 0.61). The overall response rate was 33.1% in the sequential treatment arm and 51.7% in the combination treatment. Conclusions: The findings support the extension of the sequential treatment starting from fluoropyrimidine plus bevacizumab to selected patients who do not need an objective response to the threatening disease. Highlights: The sequential arm showed superiority in the primary end-point, time to failure of strategy. Overall survival was no difference between the sequential and combination arms. Overall response was 20% more in the combination arm. The sequential approach could cover selected patients with no need for shrinkage.